Strategic Management Accounting Survey: Overhead Cost Allocation & Performance Evaluation Practices of Australian Manufacturers. - Liao, Shu S. (The Accounting Review, 1993)
Abstract Reviews the book "Strategic Management Accounting Survey: Overhead Cost Allocation and Performance Evaluation Practices of Australian Manufacturers," by Graeme W. Dean, Marc P. Joye and Paul J. Blayney.